Sistem Informasi Administrasi Pelayanan Parkir Pada Dinas Perhubungan Kota Batam - Muhammat Rasid Ridho; Fifi Fifi (LPPM Universitas Putera Batam, 2022)
In accordance with Government Regulation Number 82 of 2012 concerning the Implementation of Electronic Systems and Transactions, in carrying out the duties and functions of the Batam City Transportation Service, it is necessary to receive support and attention from the community in order to evaluate performance through the services provided by the Transportation Service as expected by all parties. The research method uses the stages: planning, analysis, design, and implementation. Currently, Laravel is the most widely used framework. This PHP framework is becoming a trend for web programmers today. It is hoped that the various features in Laravel can make it easier to make this application. Features such as: Composer, Routing which will determine what response must be done to reply to requests, Artisan which facilitates database migration, manages application namespaces, interacts through applications through Tinker. Migration has the advantage of simply creating a class, this class is usually used to create databases for various RDBMS and all changes that we make to the database are recorded in a separate database table.